Efektivitas Penerapan Hak-Hak Tersangka/Terdakwa Dalam Proses Penyidikan Perkara Pidana: Studi Di Kejaksaan Negeri Wajo - Andi Kalsum; Baharuddin Badaru; Hamza Baharuddin (Journal of Lex Generalis (JLG), 2020)
Tujuan penelitian ini adalah: 1) Untuk menganalisis faktor-faktor yang mempengaruhi efektivitas penerapan hak-hak tersangka/terdakwa dalam proses penyidikan perkara pidana di Kejaksaan Negeri Wajo. 2) untuk menganalisis efektivitas penerapan hak-hak tersangka/terdakwa dalam proses penyidikan perkara pidana di Kejaksaan Negeri Wajo. Hasil penelitian menunjukkan: 1) Faktor hukum, Faktor Penegak hukum, Faktor kebudayaan, Faktor sarana atau fasilitas pendukung, dan Faktor masyarakat berpengaruh terhadap efektivitas penerapan hak-hak tersangka/terdakwa dalam proses penyidikan perkara pidana di Kejaksaan Negeri Wajo. 2) Efektifitas penerapan hak-hak tersangka/terdakwa berdasarkan faktor hukum, faktor penegak hukum, faktor kebudayaan, faktor sarana atau fasilitas pendukung, dan faktor masyarakat dalam proses penyidikan perkara pidana di Kejaksaan Negeri Wajo terlaksana kurang efektif. The research aims to: To find out the implementation of the imposition of a criminal payment of substitute money as an additional crime in handling cases of corruption, especially in the jurisdiction of the District Attorney Office , and provide solutions regarding the obstacles encountered. This type of research is empirical juridical, the data obtained by the author from the study of documents and interviews with interested parties in this case the Sragen District Attorney's Office, then conducted a qualitative descriptive analysis. The research results of the authors find that: Material criminal law against the abuse of authority in corruption is the element to benefit oneself or others and also the abuse of authority, opportunity or means available because of position and position, as well as can harm the country's finances or the economy country. Abuse of authority in corruption can be accounted for by two legal concepts, namely the concept of state administrative law and criminal law.